Trends on Educational Gamification: Challenges and Learning Opportunities - Piñero Charlo, José Carlos; Costado Dios, María Teresa; Carmona Medeiro, Enrique; Lloret, Fernando (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Games are a natural activity-we all know how to play. Perhaps this is the key feature that explains the increase in the use of game-based learning (GBL) strategies: Applying games to education converts education into a universal activity. Over the last ten years, the way in which education and training is delivered has considerably changed, not only due to a new technologic environment-plenty of social networks, MOOCs, etc.-but also because of the appearance of new methodologies. Such new methodologies are shifting the center of gravity: from the teacher to the student, with the aim of awakening relational aspects, as well as promoting imagination and divergent thinking. One new approach that holds considerable promise for helping to engage learners is, indeed, game-based learning (GBL). However, while a growing number of institutions are beginning to see the validity of GBL, there are still many challenges to overcome before this type of learning can become widespread.In this Special Issue, we want to gather several studies and experiences in GBL to be shared with other teachers and researchers.